Curriculum-Based Love as Innovative Learning in Madrasahs - Herdiana Herdiana; Ratna Sari; Fauzan Siregar (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
The Love-Based Curriculum (Kurikulum Berbasis Cinta, KBC) is a revolutionary policy initiative rolled out by Indonesia’s Ministry of Religious Affairs and officially launched on 24 July 2025 to present a more humanistic, inclusive and spiritually grounded model of madrasah education. The implementation of this curriculum at the Madrasah Ibtidaiyah (MI) level has its own challenges and opportunities, given the need to address the developmental characteristics of elementary school children. The study adopts a literature review approach to explore the policy framework and implementation of KBC in MI drawing on previous research and official policy documents. KBC is based on the Decree of the Minister of Religious Affairs No. 1503/2024 and the Decree of the Director General of Islamic Education No. 6077/2025 based on 46 sources formed on five core values (Panca Cinta), namely love for God, knowledge, self and others, the environment, and the homeland. The results of the study show that the implementation of KBC can improve character building, reduce intolerance, improve empathy, and promote students’ learning independence. But there remain hurdles around teacher preparedness, lack of resources and pushback against change from traditional ways of teaching. The study concludes that KBC’s effectiveness largely depends on the teachers’ capacity as role models, humanistic administration and supervisory support, and integration of immersive learning, blended learning and child-friendly digital technologies.